PENGARUH LATIHAN PEREGANGAN TERHADAP PENURUNAN INTENSITAS NYERI PADA PERAWAT YANG MENDERITA LOW BACK PAIN (LBP) - Wiwit ' Nurdiati; Gamya Tri Utami; Sri ' Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract This study aimed to determine the effect of stretching exercises to decrease pain intensity on a nurse who suffered from LBP . This study used a quasi experiment research design with pretest - posttest control group. The number of samples taken is 30 people and is divided into 2 groups: 15 in the experimental group and 15 control group . Nurse pain intensity was measured using observation sheet Numeric Rating Scale ( NRC ). Analysis of the research is the analysis of univariate and bivariate . Based on the results of independent t-test showed a significant difference in pain intensity after the LBP given stretching exercises with a p value of 0.000 ( p < 0.05 ), so in this study showed that there was an effect of stretching exercises to decrease the intensity of pain in nurses suffering from LBP . Keywords: LBP, nurses, pain, streching exercises